Estudo da resistência de aderência na alvenaria de blocos de concreto celular autoclavado - Ferreira, Gustavo Rangel de Sousa (2023)
This work focuses on the field of building materials and focuses on the study of adhesion resistence in substrates made of autoclaved aereted concrete blocks. The main reason for this study is due to the fact that this material has been increasingly used in Brazilian building construction, due to its low thermal conductivity and small specific mass, despite its large dimensions. In this work, a masonry wall of autoclaved aereted concrete blocks was executed and one of the faces was coated with a roughcast layer followed by plastering with mixed mortar (cement and lime), while the other side was used only the plaster layer. Then, the normal traction test was carried out with a dynamometer and the adhesion resistance for the faces was calculated. For the face that received the roughcast layer, 0,21 MPa was obtained, and for the face with only roughcast, the bond strength was 0,15 MPa. With these results in hand, a comparison was made with the values required by ABNT NBR 13749 (2013) and values from previous works. It was found that the values achieved in this research were lower than those prescribed in regulations and for ceramic block substrates. When compared with works by other authors for BCCA substrate, the result was 650% more satisfactory. Finally, it was concluded that in order for this material to perform better in terms of adhesion, in addition to the roughcast layer being necessary, it is also important to carry out a surface treatment prior to performing the mortar coating.